Prototype of IoT-Based Temperature and Humidity Monitoring and Controlling System for Broiler Chicken Coops - Lengkong, Oktoverano; Tombeng, Marchel Thimoty; Tasidjawa, Jeniffer Linda; Birahy, Brian Gustaf (Fakultas Ilmu Komputer, Universitas Klabat, 2025)
Temperature and humidity are critical factors that influence the health and productivity of broiler chickens. Manual monitoring and control of coop conditions are often ineffective and inefficient, leading to a decline in production quality. This research aims to develop a prototype IoT-based monitoring and controlling system for temperature and humidity in broiler chicken coops. The system employs a DHT22 sensor to measure temperature and humidity, a Wemos D1 R1 microcontroller for data processing, and the Blynk application as a user interface for real-time monitoring and notifications. The Evolutionary Prototyping method is applied in the development of this system to allow gradual adjustments based on user needs. Testing results show that the prototype can monitor temperature and humidity in real-time and automatically activate fans or lights when the temperature is outside the optimal range. With this system, farmers can monitor coop conditions remotely, simplifying farm management.